Combination therapy with sulfasalazine and methotrexate is more effective than either drug alone in patients with rheumatoid arthritis with a suboptimal response to sulfasalazine: results from the double-blind placebo-controlled MASCOT study. Issue 2 (22nd August 2006) - Capell, Hilary A; Madhok, Rajan; Porter, Duncan R; Munro, Robin A L; McInnes, Iain B; Hunter, John A; Steven, Malcolm; Zoma, Asad; Morrison, Elaine; Sambrook, Martin; Wui Poon, Fat; Hampson, Rosemary; et al.
Abstract : Background: Optimal use of disease-modifying antirheumatic drugs (DMARDs) in rheumatoid arthritis is vital if progression of disease is to be reduced. Methotrexate (MTX) and sulfasalazine (SASP) are widely used inexpensive DMARDs, recently often combined despite no firm evidence of benefit from previous studies. Aim: To establish whether a combination of SASP and MTX is superior to either drug alone in patients with rheumatoid arthritis with a suboptimal response to 6 months of SASP. Methods: A randomised controlled study of step-up DMARD treatment in early rheumatoid arthritis. In phase I, 687 patients received SASP for 6 months. Those with a disease activity score (DAS) ⩾2.4 were offered additional treatment in phase II (SASP alone, MTX alone or a combination of the two). The primary outcome measure was change in DAS. Results: At 6 months, 191 (28%) patients had a DAS <2.4, 123 (18%) were eligible but did not wish to enter phase II, 130 (19%) stopped SASP because of reversible adverse events and 165 (24%) entered phase II. DAS at 18 months was significantly lower in those who received combination treatment compared with those who received either SASP or MTX: monotherapy arms did not differ. Improvement in European League Against Rheumatism and American College of Rheumatology 20, 50 and 70 scores favoured combination therapy. Conclusions: In this "true-to-life" study, an inexpensive combination of DMARDs proved more effective than monotherapy in patients with rheumatoid arthritis with a suboptimal response to SASP. There was no increase in toxicity. These results provide an evidence base for the use of this combination as a component of tight control strategies.